Steam injection pressures and rates, variable permeabilities systems, and wells alignments parameterization in SAGD: A simulation study - Zhengbin Wu; Morice Richard Mworia; Kun Shu; Yuhang Ren; Qiyang Gou; Shu Jiang; Zhangxin Chen (Unconventional Resources)
SAGD is one of the steam recovery methods of heavy oil, which is typically performed using one horizontal injection well and one horizontal production well. However, multiple injection and production wells might also be utilized. Recently, studies of this method involving steam injection rate and pressure parameterization were performed over limited ranges of these parameters, with limited knowledge of steam injection rate characterization based on different levels of average homogeneity and heterogeneity of permeability systems. Moreover, there are no simulation studies of vertical injectors and multiple horizontal injection wells, or steam injection rates characterization. This paper examines these limitations considering the reservoir and fluid properties of the Liaohe heavy oil field in China. It is revealed that elevating pressures for a given steam injection rate do not have a significant impact on heavy oil recovery performance factors. A recommendation of injection at slightly higher than the initial reservoir pressure (6.3 MPa), which is 6.5 MPa to compensate for steam compression costs. Increasing the steam injection rate within a limited range provides a larger volume for the steam chambers that raise the average reservoir temperature and result in higher oil recovery factors. The positive-rhythm reservoir (permeability rises from the top to the bottom of the reservoir) extracts more oil than that of the negative-rhythm one (permeability decreases from the top to the bottom of the reservoir). The vertical injector has better oil-sweep efficiency compared with the horizontal injector due to more expandable steam chambers with a very small steam chamber rising stage. Two horizontal injectors at the same total steam injection rate as conventional SAGD enhance the oil recovery factor (an increment of up to 15.24 %) and reduce cumulative steam-oil ratio by 3.64.